Simulation and validation of thermography inspection for components produced by additive manufacturing - Carvalho, Marta S. (2019)
Authors gratefully acknowledge the funding of Project POCI-01-0145-FEDER-016414 (FIBR3D), cofinanced by Programa Operacional Competitividade e Internacionalização and Programa Operacional Regional de Lisboa , through Fundo Europeu de Desenvolvimento Regional (FEDER) and by National Funds through Fundação para a Ciência e a Tecnologia (FCT - MCTES). MSC and TGS acknowledge FCT - MCTES for its financial support via the project UID/EMS/00667/2019 (UNIDEMI).